Monomers for Adhesive Polymers 12 Synthesis and Free‐Radical Homo‐ and Copolymerization of 2‐Ethoxycarbonylallyl 5‐(1, 2‐dithiolane‐3‐yl)‐pentanoate. Issue 11 (28th January 2013) - Pavlinec, Juraj; Kleinova, Angela; Angermann, Jörg; Lamparth, Iris; Moszner, Norbert
Abstract The 2‐ethoxycarbonylallyl 5‐(1, 2‐dithiolane‐3‐yl)‐pentanoate monomer (AODS) includes in its molecular structure CC and SS reactive bonds allowing it to behave as a bi‐functional monomer, possessing two groups, however, with different reactivity for use in polymer chain building. The polymerization‐specific features of this monomer are the absence of auto‐acceleration and polymer chain crosslinking. Polymerization proceeds readily through most free‐radical initiators. One exception, carboxy‐peroxides are rapidly decomposed without the production of free radicals. AODS is partially converted to a gel without the consumption of double bonds during monomer dissolution in certain organic solvents and after being mixed in solution with carboxy‐peroxides. The determined AODS‐co‐MMA copolymerization parameters are r1 = 2.61, r2 = 0.23 if Luperco peroxide is used as a polymerization initiator, and r1 = 2.71, r2 = 0.38 if AIBN is used. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>